Nonexistence Results for Some Classes of Nonlinear Fractional Differential Inequalities - Mohamed Jleli; Bessem Samet (Journal of Function Spaces)
We study the nonexistence of global solutions for new classes of nonlinear fractional differential inequalities. Namely, sufficient conditions are provided so that the considered problems admit no global solutions. The proofs of our results are based on the test function method and some integral estimates.